Principles of appearance acquisition and representation - Weyrich, Tim; Lawrence, Jason; Lensch, Hendrik P.A.; Usinkiewicz, Szymon; Zickler, Todd (Foundations and Trends in Computer Graphics and Vision, 2009)
Algorithms for scene understanding and realistic image synthesis require accurate models of the way real-world materials scatter light. This study describes recent work in the graphics community to measure the spatially- and directionally-varying reflectance and subsurface scattering of complex materials, and to develop efficient representations and analysis tools for these datasets. We describe the design of acquisition devices and capture strategies for reflectance functions such as BRDFs and BSSRDFs, efficient factored representations, and a case study of capturing the appearance of human faces. © 2009.
CRIS-Team Scopus Importer:2022-07-26